Respuesta :

Answer: x = [tex]\frac{7}{2}i[/tex], 2i

Step-by-step explanation:

 2x²   - 11ix    - 14   =   0

a=2,  b=-11i, c = -14

[tex]x = \frac{-(b)+/-\sqrt{(b)^{2}-4(a)(c)} }{2(a)}[/tex]

[tex]x = \frac{-(-11i)+/-\sqrt{(-11i)^{2}-4(2)(-14)} }{2(2)}[/tex]

 [tex]= \frac{11i+/-\sqrt{-121 + 112} }{4}[/tex]

 [tex]= \frac{11i+/-\sqrt{-9} }{4}[/tex]

 [tex]= \frac{11i+/-3i}{4}[/tex]

[tex]\frac{11i+3i}{4}[/tex]               [tex]\frac{11i-3i}{4}[/tex]

= [tex]\frac{14i}{4}[/tex]                   = [tex]\frac{8i}{4}[/tex]

= [tex]\frac{7i}{2}[/tex]                     = 2i